Text message-based lifestyle intervention in primary care patients with hypertension: a randomized controlled pilot trial. (2nd July 2020) - Bolmsjö, Beata Borgström; Wolff, Moa; Nymberg, Veronica Milos; Sandberg, Magnus; Midlöv, Patrik; Calling, Susanna
Abstract: Objective: To evaluate the feasibility of a randomized controlled pilot study with lifestyle-promoting text messages as a treatment for hypertension in primary care. Design: Randomized controlled pilot trial. Setting: Three primary health care centers in southern Sweden. Subjects: Sixty patients aged 40–80 years with hypertension were included. Main outcome measures: Feasibility of the pilot study, i.e. recruitment rate, dropout rate and eligibility criteria. Secondary outcomes were change in blood pressure and other cardiovascular risk factors. Methods: Thirty participants were randomized to the intervention group with four lifestyle-promoting text messages sent every week for six months. The control group received usual care. The baseline and follow-up visits for all 60 patients included measurements of blood pressure, anthropometrics, blood tests and a self-reported questionnaire. Results: All feasibility criteria (recruitment rate (≥55%), dropout rate (≤15%) and eligibility (60 eligible patients during the four-month inclusion period) for the pilot study were fulfilled. This means that a larger study with a similar design may be conducted. After six months, there were no significant improvements in cardiovascular risk factors. However, we found favorable trends for all secondary outcomes in the intervention group as compared to the control group. Conclusion: Lifestyle modification in patients with hypertension is important to reduce cardiovascular risk. However, primary healthcare has limited resources to work with modifying lifestyle habits. This is the first pilot study to test the feasibility of text message-based lifestyle intervention in patients with hypertension in Swedish primary healthcare. Whether significant improvement in cardiovascular risk factors may be achieved in a larger study population remains to be evaluated. Key points: This pilot randomized controlled trial (RCT) is the first study to evaluate the feasibility of text message-based lifestyle advice to patients with hypertension in Swedish primary healthcare. All feasibility criteria for the pilot study were fulfilled. This outcome means that a larger study with a similar design may be conducted. The study was not powered to find significant changes in cardiovascular risk factors. Nevertheless, after six months we found favorable trends for all secondary outcomes in the intervention group compared to control. If a future larger study can show significant results, this intervention could serve as a useful tool in everyday primary healthcare.